2018
DOI: 10.1111/rda.13382
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity induced using high ambient temperature during embryogenesis in domesticated zebrafish, Danio rerio

Abstract: Contents Ambient temperature during early stages of life has a substantial effect on physiological processes, eliciting phenotypic plasticity during zebrafish developmental stages. Zebrafish are known to possess a noteworthy ability to modify their phenotype in dependence of environmental factors. However, there is a poor understanding of the effects of temperature during embryogenesis, which influences the biological functions such as survival ability and masculinization in later developmental stages. Since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 40 publications
13
27
0
Order By: Relevance
“…The standard rearing temperatures for zebrafish are between 26–29°C with an optimum of 28°C (Detrich, Zon, & Westerfield, ; Ribas & Piferrer, ). The high temperature applied in the temperature‐exposed group of this study is in line with previously reported studies (Hosseini, Brenig, et al, ; Hosseini, Ha, et al, ; Abozaid et al, ). The temperature of heat‐exposed groups was changed gradually in this experiment.…”
Section: Methodssupporting
confidence: 91%
See 4 more Smart Citations
“…The standard rearing temperatures for zebrafish are between 26–29°C with an optimum of 28°C (Detrich, Zon, & Westerfield, ; Ribas & Piferrer, ). The high temperature applied in the temperature‐exposed group of this study is in line with previously reported studies (Hosseini, Brenig, et al, ; Hosseini, Ha, et al, ; Abozaid et al, ). The temperature of heat‐exposed groups was changed gradually in this experiment.…”
Section: Methodssupporting
confidence: 91%
“…Schnurr, Yin, and Scott () also observed a higher growth rate in zebrafish treated with high temperature during embryonic development compared to the control group. Our previous study confirms this too; a positive effect of increased temperature during embryogenesis on growth rate of another zebrafish strain was observed, which was more pronounced in females than in males (Hosseini, Brenig, et al, ). Embryonic temperature in zebrafish affects thermal acclimation of muscle tissue, which has an influence on energy metabolism and swimming performance in adult fish, due to differences in the expression of genes involved in energy metabolism, cell stress, muscle contraction, and apoptosis (Scott & Johnston, ).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations